2008
DOI: 10.1007/s00216-008-2244-0
|View full text |Cite
|
Sign up to set email alerts
|

Substrate binding to cytochromes P450

Abstract: P450s have attracted tremendous attention due not only to their involvement in the metabolism of drug molecules and endogenous substrates but also the unusual nature of the reaction they catalyze, namely the oxidation of unactivated C-H bonds. The binding of substrates to P450s, which is usually viewed as the first step in the catalytic cycle, has been studied extensively via a variety of biochemical and biophysical approaches. These studies were directed towards answering different questions related to P450s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 188 publications
(222 reference statements)
5
80
2
2
Order By: Relevance
“…From these results, it would be reasonable to consider that UGT2B7 suppresses CYP3A4 activity by inhibiting the insertion of substrates into the catalytic pocket of CYP3A4. The binding of substrate to P450 causes a change in its electrical potential, and this change drives the catalytic cycle of P450 (Isin and Guengerich, 2008). If UGT2B7 inhibits this first step, CYP3A4 function would be suppressed in all the later catalytic steps as we observed.…”
Section: Ugt2b7 Suppresses Cyp3a4 Functionsupporting
confidence: 53%
“…From these results, it would be reasonable to consider that UGT2B7 suppresses CYP3A4 activity by inhibiting the insertion of substrates into the catalytic pocket of CYP3A4. The binding of substrate to P450 causes a change in its electrical potential, and this change drives the catalytic cycle of P450 (Isin and Guengerich, 2008). If UGT2B7 inhibits this first step, CYP3A4 function would be suppressed in all the later catalytic steps as we observed.…”
Section: Ugt2b7 Suppresses Cyp3a4 Functionsupporting
confidence: 53%
“…Co-crystallization of progesterone with 3A4 identified a peripheral binding site for the steroid near the outer surface of helices FЈ and GЈ and the phenylalanine cluster (68). 3A4 often exhibits homo-and heterotropic activation kinetics with progesterone and other substrates of similar size that are consistent with the binding of two or more molecules to the enzyme (73,74). Biophysical studies have suggested that two molecules can stack in the active site (75), as seen for the 3A4 structure with two molecules of ketoconazole (69), and have provided evidence for a peripheral binding site such as that observed for progesterone (76).…”
Section: Drug-metabolizing Enzymesmentioning
confidence: 82%
“…Binding of substrates and xenobiotics to P450s can result in two types of characteristic spectral changes in the UV/VIS heme Soret spectrum, referred to as Type I and Type II (Schenkman et al, 1981;Isin and Guengerich, 2008). A classical Type I spectrum results from the spin-state shift of the Soret band at about 418 nm that represents the ferric (Fe III ) low-spin substrate free form tõ 390 nm for the ferric (Fe III ) high-spin form originating from the displacement of H 2 O as the sixth ligand when a substrate is bound in close proximity to the heme.…”
Section: Determination Of Spectral Dissociation Constantsmentioning
confidence: 99%
“…A classical Type I spectrum results from the spin-state shift of the Soret band at about 418 nm that represents the ferric (Fe III ) low-spin substrate free form tõ 390 nm for the ferric (Fe III ) high-spin form originating from the displacement of H 2 O as the sixth ligand when a substrate is bound in close proximity to the heme. Direct coordination of a ligand to heme iron results in a Type II spectrum characterized by a shift to 430-455 nm, but these complexes are inhibitory and generally not considered relevant to productive substrate binding leading to catalysis (Isin and Guengerich, 2008).…”
Section: Determination Of Spectral Dissociation Constantsmentioning
confidence: 99%